An Exploratory Study of Teaching Tasks in English as a Foreign Language Education. Issue 1 (4th December 2017) - Turkan, Sultan; Timpe-Laughlin, Veronika; Papageorgiou, Spiros
Abstract: Due to rising demand for qualified teachers of English as a foreign language (EFL), interest in issues pertaining to the language proficiency of these teachers has increased. However, research focusing on the teaching tasks that EFL teachers engage in for the purposes of EFL instruction is scant. The present study aims to address this gap in the literature by identifying the teaching tasks and exploring the teaching practices reported in logs kept by 5 EFL teachers over the course of a 2‐week period. Findings suggest that the majority of language teaching tasks observed in the teachers' logs were related to the instructional stages of (a) presenting subject material and communicating lesson content and (b) planning, developing, and organizing instruction. Abstract : Report Number: ETS RR‐17–56